Exploring manzamine a: a promising anti-lung cancer agent from marine sponge Haliclona sp - Su, Min; Zhu, Jie; Bai, Luyuan; Cao, Yu; Wang, Shaohui (Frontiers in Pharmacology, 2025)
Manzamine A (MA), a bioactive compound derived from the marine sponge Haliclona sp., shows considerable therapeutic potential, particularly in the treatment of various cancer types. Extracted with acetone and purified through chromatography, MA exhibits a bioavailability of 20.6% when administered orally in rats, underscoring its feasibility for therapeutic use. This compound disrupts key cellular mechanisms essential for cancer progression, including microtubule dynamics and DNA replication enzymes, demonstrating strong anti-proliferative effects against multiple cancer cell lines while sparing normal cells. Additionally, network pharmacology and molecular docking studies reveal MA’s interactions with important targets related to lung cancer progression, such as EGFR and SRC, bolstering its potential as a novel anti-lung cancer agent. Pathway analyses further indicate that MA influences critical signaling pathways involved in tumor growth and metastasis. Given the urgent need for effective treatments against drug-resistant cancers and the limited toxicity profile of MA, further exploration of its pharmacological benefits and mechanism could pave the way for new therapeutic strategies in lung cancer.